Effect of thermal aging on the electrical resistivity of Fe-added SAC105 solder alloys. Issue 9 (August 2015) - Sabri, M.F.M.; Nordin, N.I.M.; Said, S.M.; Amin, N.A.A.M.; Arof, H.; Jauhari, I.; Ramli, R.; Weide-Zaage, K.
Abstract: The ternary Sn–1.0Ag–0.5Cu (SAC105) solders doped with a minor addition of Fe (0.1, 0.3 and 0.5 wt.%) have been shown to demonstrate excellent mechanical thermal cyclic reliability. To complement the mechanical performance, the electrical resistivities of SAC105, SAC105–0.1Fe, SAC105–0.3Fe, and SAC105–0.5Fe bulk solder alloys were also characterised after thermal aging. Results showed that the overall resistivity decreased by up to 13% after the thermal aging process. Meanwhile the electrical resistivity for 0.1 wt.%, 0.3 wt.%, and 0.5 wt.% Fe-bearing SAC105 solder alloys decreased by 25%, 11%, and 17% respectively, showing a rather stable reduction in resistivity. This can be correlated to the stabilisation of the microstructure of the Fe-added SAC 105 after thermal aging. Highlights: The addition of Fe to SAC105 suppresses coarsening of Ag3 Sn in thermal aging. Overall resistivity of Fe-added SAC105 decreased after thermal aging. Fe-added SAC105 has a stable microstructure during thermal aging that encourages improvement of electrical resistivity.